Memorandum on social insurance and allied services in their bearing on neurotic disorder
1943 1943 1940s 19 pages 18 There should be arrangements for the psychiatrist to review persons with a persistent illness whenever there is doubt whether this illness is sufficient physical cause for their disability. (15) The scheme envisages various methods, e.g. placement by employment exchanges, retraining and rehabilitation, for facilitating re-entry into employment, and these will need co-ordination. The normal method of re-entry the employment exchange should entail some form of vocational guidance, and a social worker should co-ordinate this with the other methods mentioned, since the whole procedure involves matching what is medically advisable to what is available. REFERENCES. BAKKE, E.W. (1933), The Unemployed Man. London : Nisbet. BRAIN, W.R. (1942), Proc. Roy. Soc. Med., 35, 295. DUBLIN, L.I., and BUNZEL, B. (1933), To Be or Not To be: A Study of Suicide. New York: Smith & Haas. EISENBERG, P., and LAZARSFELD, P.E. (1936), Psychol. Bull., 30, 358. HALLIDAY, J. E. (1935), Brit. Med. J. Supplt. pp. 85 and 99. HART, B. (1942), Proc. Roy. Soc. Med., 35, 495. LAZARSFELD, JAHODA, M., and ZEISL, H. (1933), Die Arbeitslosen von Marienthal. Leipzig. (Abbrev. in Char. and Personality, 1932-3, 1, 147). LEWIS, A.J. (1935), Lancet, ii, 293. Men Without Work. Pilgrim Trust Report, 1938. London : Cambridge University Press. PATERSON, D.C., and DARBY, J.G. (1936), Men, Women and Jobs. Minneapolis : University of Minneapolis Press. Social Problem Group. Edited by C.P. Blacker. London : Oxford University Press. WILSON, A., and LEVY, H. (1939 and 1941), Workmen's Compensation, vols. 1 and 2. London. Made and printed in Great Britain by Adlard & Son, Ltd., at their works, Bartholomew Press, Dorking 292/847/2/174